Development of Electronic Identification Measures in the Public Sector in Lithuania: Reality, Demand and the Future - Rimantas Petrauskas; Paulius Vaina (Social Technologies, 2012)
Purpose—to analyze eIAS implementation reports and development peculiarities; to discuss measures that impede effective implementation of eIAS in Lithuania.Design/methodology/approach—logical and systematic analysis, meta-analysis.Findings—the article discusses the integration and use of eIAS solutions by the public sector in Lithuania. Main findings: 1) eIAS products and services are an integral part of a complex heterogeneous national platform consisting of regulatory, technical, organizational, social and even practical challenges; 2) National environment for eIAS remains underdeveloped for real life usage and promotion in order to reach critical mass applicability; 3) possibility to use different levels of eIAS for public e-Services is vital for the development of e-Government.Research limitations/implications—the general overview reveals implementation challenges and particularities of the eIAS in the public sector of Lithuania. The article does not analyse the exploitation stages of eIAS.Practical implications—the article evaluates regulatory, organizational, social and practical peculiarities of eIAS introduction and use in the public sector in Lithuania. The article forms a basis in order to exploit eIAS products and services more effectively.Originality/Value—offers insight into the eIAS topic and fills the information void of implementation of eIAS solutions in the public sector, as it is not widely analysed in Lithuania.Research type: general review, viewpoint.